RELEVANSI KONSEP MAQASHID SYARIAH PADA PEMASARAN SYARIAH DALAM PANDANGAN IMAM ASY-SYATIBI - Lara Aziza Putri; Miftahul Zikri Sy (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the relevance of the concept of maqashid sharia in sharia marketing in the view of Imam Asy-Syatibi. The concept of maqashid sharia was popularized by Imam Asy-Syatibi with the concept of "indeed sharia aims for the welfare of the world and the hereafter". This study uses a systematic literature review approach through this process, various articles and journals related to the keywords "Islamic Economics", "Imam Asy-Syatibi, Sharia Marketing", and "Social Justice" are collected, filtered, and evaluated. The results of the study show that the results of this study indicate that the relevance of maqashid sharia in sharia marketing is very related, where the four characteristics of sharia marketing must always be guided by maqashid sharia. This is evidenced by the four characteristics reviewed from the perspective of maqashid sharia. Where teisties or rabbaniyah are included in the elements of religious protection (hifdz din) and soul protection (hifdz nafs), ethics or akhlaqiyah enter into the protection of reason (hifdz 'aql), realistic or al-waqiyah enter into the protection of property (hifdz maal) and finally humanism which enters into the protection of offspring (hifdz nasl).